Chemistry technology research to produce meat enriched with biologically active carbohydrates - Kh, Badamtsetseg; B, Munkhjargal (Bulletin of the Institute of Chemistry and Chemical Technology, 2018)
Brewery’s spent grain is the main by-product of the brewing industry. The effects of replacing fat with arabinoxylan fraction of BSG for physicochemical, textural properties and sensory evaluations of reduced-fat sausages are evaluated. Control was prepared with 15% fat, and three reduced-fat sausages were formulated with 5, 10 and 15% arabinoxylan fraction (T1 sausage with 5% of arabinoxylan fraction + 10% of fat, T2 sausage with 10% of arabinoxylan fraction + 5% of fat and T3 sausage with 15% of arabinoxylan fraction + 0% of fat). With increasing arabinoxylan fraction content in the sausage, the fat content and food calories are decreased in reduced-fat sausages. Биологийн идэвхт нүүрсусаар баяжуулсан махан хүнс гарган авах хими-технологийн судалгаа Хураангуй: Пивоны шаар нь шар айрагны үйлдвэрийн гол дайвар бүтээгдэхүүн юм. Пивоны шаар нь арабиноксиланаар баялаг бөгөөд шүлтийн хандлалтаар гарган авч бүтээгдэхүүнд нэмж туршилтын үр дүнг харьцуулан гаргасан. Зайдасны 4 дээж бэлдсэн. Хяналт (пивоны шаар/арабиноксилан 0%, гахайн өөх 15%), Д1 (пивоны шаар/арабиноксилан 5%, гахайн өөх 10% нэмсэн), Д2 (пивоны шаар/арабиноксилан 10%, гахайн өөх 5%), Д3 (пивоны шаар/арабиноксилан 15%, гахайн өөх 0%). Зайдсанд гахайн өөхийг багасгаж шаараар орлуулснаар тослогийн агууламж, илчлэг чанар буурсан. Түлхүүр үгс: пивоны шаар, арабиноксилан, тослогийн агууламж